2020
DOI: 10.3390/su12104318
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Reliability Model Verification in the Crisis Escalation Phase Caused by the COVID-19 Pandemic

Abstract: This article concerns the Organizational Reliability Model (ORM) verification in the crisis escalation phase caused by critical conditions of organization functioning induced by the COVID-19 pandemic. ORM is constituted by three reliabilities, human resources, information technology, and management, which are mediators through which Type-1 and Type-2 reliability capabilities influence organizational reliability. Organizational reliability is a prerequisite for sustainability of contemporary organizations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…In the uncertain conditions caused by COVID-19, in order to create safe and reliable conditions in the organization, it is necessary to pay attention to the three pillars of reliability, which include human resources, information technology, and management in general and not separately. [ 42 ]. Human resource reliability refers to the ability to anticipate and detect potential risks and problems, prevent disruptions in the performance of IT systems, maintain adequate performance, solve problems to promote effective performance and learn through experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the uncertain conditions caused by COVID-19, in order to create safe and reliable conditions in the organization, it is necessary to pay attention to the three pillars of reliability, which include human resources, information technology, and management in general and not separately. [ 42 ]. Human resource reliability refers to the ability to anticipate and detect potential risks and problems, prevent disruptions in the performance of IT systems, maintain adequate performance, solve problems to promote effective performance and learn through experience.…”
Section: Discussionmentioning
confidence: 99%
“…The manager’s reliability, however, is focused on the ability to anticipate and detect potential risks and problems that prevent the organization from reaching its goals, change in the management system to prevent disruption, restore the organization’s performance to its natural state in case of disruption, and learn from mistakes. This ratability promotes work motivation, job satisfaction, organizational values, commitment and interaction, and managers' abilities and interpersonal relationships 42 , 43 . The structure and interaction of these three pillars (human resources, information technology, and management) in the organization must change in the wake of crises.…”
Section: Discussionmentioning
confidence: 99%
“…The EDC based Model of Job Performance modified for the time of the initial phase of crisis occurring in organization due to Black Swan phenomena is presented in Figure 1. The obtained results confirmed that during the crisis caused by Black Swan, traditional models and paradigms of management indeed do not work the same (Bieńkowska, Tworek, and Zabłocka-Kluczka, 2020). Due to the predicted disruption of job performance in times of crisis, the Job Performance Model based on EDC was also verified to have a different structure (Figure 2).…”
Section: Discussionmentioning
confidence: 53%
“…However, decision makers "are mostly concerned about the cost of mistakes, rather than exact knowledge about the statistical properties" (Taleb, 2007, p. 199). Moreover, in such extreme conditions of the organization's functioning causing crisis to occur in it, traditional models and paradigms of management do not work (Bieńkowska, Tworek and Zabłocka-Kluczka, 2020) and they need to rely on changed models in order to secure proper operation in critical conditions. The procedures normally adopted in the organization and the routines and down practices are no longer sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…These two specifics (complexity of the investigated system and uncertainty of the initial data) are the principal factors that cause the development of new methods for reliability analysis in healthcare safety. The studies of healthcare safety in time of the coronavirus pandemic are restricted by uncertainties and weak knowledge even more [10,11,24]. Therefore, the methods for reliability analysis that allow analysis and evaluation based on uncertain data should be considered as the first.…”
Section: Introductionmentioning
confidence: 99%